2017
DOI: 10.1111/ceo.13006
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state pattern electroretinogram and short‐duration transient visual evoked potentials in glaucomatous and healthy eyes

Abstract: Steady-state pattern electroretinogram was effectively able to discern between glaucomatous and healthy eyes. Steady-state pattern electroretinogram may thus have a role as a clinically useful electrophysiological diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…With regard to the relationships between the clinical measures and DTI metrics for DON, for each part of the Interestingly, the FA and MD of almost all segments of the visual pathway were related to the amplitude and latency of the VEPs, which are signals obtained from electroencephalographic activities 38 that can reflect the functional integrity of the visual pathway. 39 However, pVEP (the delayed P100 latent time and/or reduced P100 amplitude) reflects the absolute value of cortical potentials evoked by patterned stimuli, which are prone to fluctuations and are affected by the interference of external noise.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relationships between the clinical measures and DTI metrics for DON, for each part of the Interestingly, the FA and MD of almost all segments of the visual pathway were related to the amplitude and latency of the VEPs, which are signals obtained from electroencephalographic activities 38 that can reflect the functional integrity of the visual pathway. 39 However, pVEP (the delayed P100 latent time and/or reduced P100 amplitude) reflects the absolute value of cortical potentials evoked by patterned stimuli, which are prone to fluctuations and are affected by the interference of external noise.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that short-term wear of the MPD, and subsequent IOP reduction, can produce an acute, statistically significant (p = 0.023) improvement in the MagD value evident on ss-pERG, suggesting an acute improvement in RGC function. Recent studies have demonstrated the MagD value to be the most accurate and valuable ss-pERG parameter for discerning glaucomatous dysfunction [12]. There was also an improvement in the MagD/Mag ratio parameter, but the difference did not reach statistical significance (p = 0.059), likely because of small sample size.…”
Section: Discussionmentioning
confidence: 91%
“…Steady-state pattern electroretinography (ss-pERG) is a tool that enables assessment of RGC function from the central 10-15°of the fovea, providing in vivo, electrophysiological measurements that are objective, rapid, repeatable, and non-invasive. Prior studies evaluating ss-pERG show functional abnormalities in ocular hypertension (OHT), glaucoma suspect, and open angle glaucoma (OAG) patients prior to clinically evident structural RGC changes [5][6][7][8][9][10][11][12][13][14][15]. Clinical standards for ss-pERG yield reliable information [16][17][18] and are beneficial as an adjunct in stratifying risk/managing glaucoma suspects [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…VEPs are visually evoked electrophysiological signals obtained from EEG activity in the visual cortex that can reflect the integrity of the entire visual pathway from the retina to the occipital cortex [ 6 ]. VEP tests have been used in glaucoma research and have been shown to offer potential diagnostic value [ 3 , 27 , 28 , 29 , 30 ]. Increased P100 latency and decreased P100 amplitude in PVEPs have both been reported in glaucoma subjects in previous studies [ 3 , 4 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%